Alkyne [2+2+2]-cyclotrimerization approach for synthesis of 6,7-cyclopropylallocolchicinoids - More, Atul A.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2016)
Employing a cobalt-catalyzed [2 + 2 + 2] alkyne cyclotrimerization as the final step, the short and efficient synthesis of cyclopropylallocolchicinoid and its analogues having functional group variations at C9 and/or C10 and C11 of ring C has been accomplished.